A profiled carrier transport layer and a method for manufacturing a solar cell

CN116471904BActive Publication Date: 2026-10-30LONGI GREEN ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310407304.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-17
Publication Date
2026-10-30
Estimated Expiration
2043-04-17

AI Technical Summary

Technical Problem

由于绒面结构限制,一般采用旋涂方式制备空穴传输层或电子传输层,但是随着绒面尺寸增大,溶液在微观尺度下强大的表面张力作用,使有机分子无法通过简单的旋涂和浸泡的方式完全覆盖绒面结构,导致大绒面结构无法有效制备得到高效的钙钛矿/硅基叠层太阳能电池

Benefits of technology

[0023]本申请提供的仿形载流子传输层的制备方法,在具有绒面结构的基底上涂覆载流子传输材料溶液,然后在该溶液的表面覆盖柔性薄膜,并在加热过程中缓慢将该柔性薄膜揭起,由于溶液在表面张力的作用下附着在所述柔性薄膜与基底之间形成一个弧形溶液聚集区域,这个区域使绒面结构的底部与顶部的溶液量分布均匀,这保证了后续溶剂挥发过程的均匀性,因此在挥发过程中,所述绒面结构的塔顶部与底部的溶剂挥发速率接近,避免了所述绒面结构的塔顶部的快速挥发及所述绒面结构的塔尖露出导致器件性能下降,最终形成厚度均匀的载流子传输层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116471904B_ABST
    Figure CN116471904B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a profiled carrier transport layer, which comprises the following steps: coating a carrier transport material solution on a substrate with a velvet structure; covering a flexible film on the liquid surface of the carrier transport material solution and heating; during the heating process, the flexible film is lifted from one side and peeled along the velvet structure; the solvent in the carrier transport material solution between the flexible film and the substrate volatilizes, the solute is deposited on the velvet structure of the substrate, and the carrier transport layer is formed. The application also provides a preparation method of a solar cell. According to the method, the flexible film is covered on the substrate coated with the carrier transport material solution, and the flexible film is slowly lifted during the heating process; due to the adhesion of the solution between the flexible film and the substrate under the action of surface tension, the solution amounts of the top and the bottom of the velvet structure are close, and finally the carrier transport layer with uniform thickness is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of solar cell technology, specifically to a contoured carrier transport layer and a method for fabricating solar cells. Background Technology

[0002] Perovskite / silicon tandem solar cells are solar cells formed by connecting a perovskite top cell with a matched bandgap and a silicon-based bottom cell in series. Compared with single-junction perovskite solar cells and silicon-based solar cells, tandem solar cells can reduce the heat loss of photogenerated carriers, thus making more comprehensive use of photon energy and achieving higher photoelectric conversion efficiency.

[0003] Currently, in perovskite / silicon tandem solar cells, hole transport layers or electron transport layers are fabricated based on the textured structure of silicon-based cells. Due to the limitations of the textured structure, spin-coating is generally used to prepare the hole transport layer or electron transport layer. However, as the textured surface size increases, the strong surface tension of the solution at the microscale prevents organic molecules from completely covering the textured structure through simple spin-coating and immersion. This results in large textured structures being unable to effectively fabricate high-efficiency perovskite / silicon tandem solar cells. When using methods such as magnetron sputtering, atomic layer deposition, and thermal evaporation to deposit conformal hole transport layers or electron transport layers, annealing at temperatures exceeding 200°C is usually required after deposition to improve carrier mobility. However, the annealing process causes irreversible damage to the silicon-based cell, leading to a significant decrease in the efficiency of perovskite / silicon tandem solar cells. Summary of the Invention

[0004] To address the aforementioned issues, this application proposes a method for preparing a contoured carrier transport layer. This method involves coating a carrier transport material solution onto a substrate with a textured surface, covering the surface of the solution with a flexible thin film, and slowly peeling off the flexible film during heating. Due to surface tension, the solution adheres between the flexible film and the substrate, resulting in similar solution volumes at the top and bottom of the textured structure. Consequently, during evaporation, the solvent evaporation rates at the top and bottom of the textured structure are similar, preventing rapid evaporation at the top of the textured structure and exposure of the top tip, which could lead to device performance degradation. Ultimately, a uniformly thick carrier transport layer is formed.

[0005] This application provides a method for fabricating a contoured carrier transport layer, comprising the following steps:

[0006] A solution of charge carrier transport material is coated onto a substrate with a textured surface.

[0007] A flexible thin film is covered on the surface of the carrier transport material solution and then heated;

[0008] During the heating process, the flexible film is peeled off from one side and detached along the textured surface. The solvent in the carrier transport material solution between the flexible film and the substrate evaporates, and the solute precipitates and deposits on the textured surface of the substrate to form a carrier transport layer.

[0009] Furthermore, the carrier transport layer is a hole transport layer or an electron transport layer.

[0010] Furthermore, the concentration of the carrier transport material solution is 0–200 mg / ml, but excluding 0.

[0011] Furthermore, the carrier transport material solution comprises a solvent and a carrier transport material.

[0012] The boiling point of the solvent does not exceed 150°C.

[0013] At 20°C, the saturated vapor pressure is greater than 1.

[0014] Further, the solvent is selected from one or more of ethanol, isopropanol, 2-butanol, water, diethyl ether, 2-methoxyethanol, ethyl acetate, methyl acetate, methyl formate, ethyl formate, tetrahydrofuran, acetonitrile, and chlorobenzene.

[0015] The charge carrier transport material is selected from SnO2, ZnO, TiO2, PCBM, and C. 60 One or more of NiO, 2PACz, 4PACz, Me-2PACz, Me-4PACz, Me-6PACz, MeO-2PACz, MeO-4PACz, MeO-6PACz, spiro-OMeTAD, and PTAA.

[0016] Furthermore, the height of the velvet structure is 1-10 μm.

[0017] Furthermore, the thickness of the flexible film is no more than 1 mm.

[0018] Furthermore, the maximum bending radius of the flexible film does not exceed 100 cm.

[0019] Furthermore, the flexible film is selected from polymer flexible films or metal flexible films.

[0020] Furthermore, after the flexible film is covered on the surface of the carrier transport material solution, it is placed on a heating plate at 50-100°C for heating. During the heating process, the flexible film is peeled off at a certain rate. Due to the surface tension, the carrier transport material solution adheres between the flexible film and the substrate, making the solution volume at the top and bottom of the textured structure on the substrate similar, thereby forming a uniformly thick contoured carrier transport layer.

[0021] Furthermore, the rate at which the flexible film is peeled off is not less than 1 cm / min.

[0022] This application provides a method for fabricating a solar cell, including the aforementioned method for fabricating a contoured carrier transport layer.

[0023] The method for preparing the contoured carrier transport layer provided in this application involves coating a carrier transport material solution onto a substrate with a textured surface, then covering the surface of the solution with a flexible film, and slowly peeling off the flexible film during heating. Due to the surface tension, the solution adheres to the flexible film and forms an arc-shaped solution accumulation region between the substrate. This region ensures a uniform solution distribution at the bottom and top of the textured structure, guaranteeing the uniformity of the subsequent solvent evaporation process. Therefore, during the evaporation process, the solvent evaporation rates at the top and bottom of the textured structure are similar, avoiding rapid evaporation at the top of the textured structure and exposure of the top tip, which could lead to a decrease in device performance. Ultimately, a carrier transport layer of uniform thickness is formed. Attached Figure Description

[0024] The accompanying drawings are provided to better understand this application and do not constitute an undue limitation thereof. Wherein:

[0025] Figure 1 This is a schematic diagram of the substrate coated with a carrier transport material solution provided in this application.

[0026] Figure 2 This is a schematic diagram of the structure of the perovskite-silicon heterojunction tandem solar cell provided in this application.

[0027] Figure 3 This is a schematic diagram of the perovskite precursor solution provided in this application before it is flipped.

[0028] Explanation of reference numerals in the attached figures

[0029] 1-First metal electrode, 2-First transparent conductive layer, 3-First doped layer, 4-First passivation layer, 5-Silicon substrate, 6-Second passivation layer, 7-Second doped layer, 8-Composite layer, 9-First carrier transport layer, 10-Shaped perovskite thin film, 11-Second carrier transport layer, 12-Second transparent conductive layer, 13-Second metal electrode. Detailed Implementation

[0030] The following description illustrates exemplary embodiments of this application, including various details to aid understanding; these should be considered merely exemplary. Therefore, those skilled in the art will recognize that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of this application. Similarly, for clarity and brevity, descriptions of well-known functions and structures are omitted in the following description. In this application, the vertical position is determined according to the direction of light incidence, with the point of light incidence being vertical.

[0031] For conventional battery devices, the thickness of the electron or hole transport layer material fabricated on the textured structure is typically less than 50 nm. The existing technology has the following drawbacks in the fabrication process:

[0032] (1) Uneven solvent evaporation leads to the exposure of the pyramid tip. During the solution coating process, the liquid film does not pass over the pyramid tip, resulting in more solution between the pyramids. Although the substrate is heated evenly, the solvent evaporation process still causes the solvent near the pyramid tip to evaporate faster, while the solvent between the pyramids and at the bottom of the pyramid evaporates slowly, resulting in uneven distribution of solute residue. As a result, the pyramid tip is exposed, and the resulting electron or hole transport layer is unevenly distributed.

[0033] (2) Limited solvent options. To obtain a uniform, conformally covered electron-hole transport layer, the solvent needs to evaporate rapidly. However, there are few solvents that can evaporate rapidly or they are toxic (such as diethyl ether, ethyl acetate, etc.). These solvents are difficult to dissolve some materials used to prepare electron or hole transport layers (such as nickel acetate, 2PACz, etc.). When a solvent with a higher boiling point (such as ethanol, dimethoxyethanol, ethylene glycol, water, etc.) is selected, the evaporation rate is slow and the evaporation process is difficult to control, which directly affects the uniformity and coverage of the film.

[0034] To address the aforementioned problems, this application provides a method for fabricating a contoured carrier transport layer, as detailed below:

[0035] This application provides a method for fabricating a contoured carrier transport layer, comprising the following steps:

[0036] Step 1: Prepare the carrier transport material solution;

[0037] Step 2: Coat the charge carrier transport material solution onto a substrate with a textured surface;

[0038] Step 3: Cover the surface of the charge carrier transport material solution with a flexible thin film and heat it;

[0039] Step 4: During the heating process, the flexible film is peeled off from one side. The solvent in the carrier transport material solution between the flexible film and the substrate evaporates rapidly, and the solute is quickly precipitated and deposited in situ on the textured surface of the substrate to form a carrier transport layer.

[0040] In this application, the carrier transport layer is a hole transport layer or an electron transport layer.

[0041] In step one, the concentration of the carrier transport material solution is 0–200 mg / ml, but not including 0. For example, it can be any value among 1 mg / ml, 5 mg / ml, 10 mg / ml, 15 mg / ml, 20 mg / ml, 25 mg / ml, 30 mg / ml, 35 mg / ml, 40 mg / ml, 45 mg / ml, 50 mg / ml, 55 mg / ml, 60 mg / ml, 65 mg / ml, 70 mg / ml, 75 mg / ml, 80 mg / ml, 85 mg / ml, 90 mg / ml, 95 mg / ml, 100 mg / ml, 110 mg / ml, 120 mg / ml, 130 mg / ml, 140 mg / ml, 150 mg / ml, 160 mg / ml, 170 mg / ml, 180 mg / ml, 190 mg / ml, and 200 mg / ml.

[0042] Specifically, the carrier transport material solution includes a solvent and a carrier transport material.

[0043] The boiling point of the solvent does not exceed 150°C, for example, it can be 150°C, 148°C, 145°C, 140°C, etc.

[0044] At 20°C, the saturated vapor pressure of the solvent is greater than 1.

[0045] Specifically, the solvent is selected from one or more of ethanol, isopropanol, 2-butanol, water, diethyl ether, 2-methoxyethanol, ethyl acetate, methyl acetate, methyl formate, ethyl formate, tetrahydrofuran, acetonitrile, and chlorobenzene, including but not limited to these.

[0046] The charge carrier transport material is selected from SnO2, ZnO, TiO2, PCBM, and C. 60The material comprises, but is not limited to, one or more of the following: NiO, 2PACz, 4PACz, Me-2PACz, Me-4PACz, Me-6PACz, MeO-2PACz, MeO-4PACz, MeO-6PACz, spiro-OMeTAD, and PTAA. Among these, 2PACz, 4PACz, Me-2PACz, Me-4PACz, Me-6PACz, MeO-2PACz, MeO-4PACz, and MeO-6PACz are used as single-molecule materials.

[0047] When the charge carrier transport material is a non-monomer material (organic or inorganic material), the concentration of the precursor solution corresponding to the charge carrier transport material is 10-200 mg / ml.

[0048] When the charge carrier transport material is an organic single-molecule material, the concentration of the charge carrier transport material solution can be 0.5-5 mg / ml.

[0049] Specifically, the height of the velvet structure is 1-10 μm, for example, it can be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm.

[0050] Specifically, the thickness of the flexible film is no more than 1 mm, for example, it can be 1 mm, 0.9 mm, 0.8 mm, 0.7 mm, etc.

[0051] The maximum bending radius of the flexible film does not exceed 100cm, and can be, for example, 100cm, 90cm, 80cm, 70cm, 60cm, 50cm, 40cm, 30cm, 20cm, 10cm, 9.5cm, 9cm, 8.5cm, 8cm, 7.5cm, etc. The maximum bending radius of the flexible film is determined by its material and its thickness.

[0052] In some embodiments, the maximum bending radius of the flexible film does not exceed 10 cm.

[0053] The flexible film is selected from polymer flexible film or metal flexible film.

[0054] The polymer flexible film can be made of polyvinyl chloride, polyethylene, polypropylene, polystyrene, polyester film, nylon film, etc.

[0055] The flexible metal film can be aluminum foil, tin foil, copper foil, etc.

[0056] In steps two and three, as follows Figure 1As shown, after the flexible film is covered on the surface of the carrier transport material solution, it is placed on a heating plate at 50-100°C for heating. During the heating process, the flexible film is peeled off at a certain rate. Due to the surface tension, the carrier transport material solution adheres to the flexible film and the substrate, making the solution volume at the top and bottom of the textured structure on the substrate similar, thereby forming a uniformly thick contoured carrier transport layer.

[0057] Specifically, the heating temperature can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, or 100°C.

[0058] In step four, the rate at which the flexible film is peeled off is 1-1000 cm / min, for example, it can be 1 cm / min, 1.1 cm / min, 1.2 cm / min, 1.3 cm / min, 1.4 cm / min, 1.5 cm / min, 1.6 cm / min, 1.7 cm / min, 1.8 cm / min, 1.9 cm / min, 2 cm / min, 5 cm / min, 10 cm / min, 20 cm / min, 30 cm / min, 40 cm / min, 50 cm / min, 60 cm / min, 70 cm / min, 80 cm / min, 90 cm / min, 100 cm / min, 200 cm / min, 300 cm / min, 400 cm / min, 500 cm / min, 600 cm / min, 700 cm / min, 800 cm / min, 900 cm / min, or 1000 cm / min.

[0059] Under constant heating temperature, if the rate at which the flexible film is peeled off is too low, the thickness of the resulting carrier transport layer film will increase, and the thickness distribution of the contoured structure on the carrier transport layer will be uneven. Under constant heating temperature, if the rate at which the flexible film is peeled off is too high, the thickness of the resulting carrier transport layer film will decrease, and it may result in the carrier transport layer film not being completely covered at the pyramid apex.

[0060] The preparation method described in this application involves coating a carrier transport material solution onto a substrate with a textured surface, then covering the surface of the solution with a flexible film, and slowly peeling off the flexible film during heating. Due to the surface tension, the solution adheres to the flexible film and the substrate, forming an arc-shaped solution accumulation region. This region ensures a uniform distribution of solution at the bottom and top of the textured structure, guaranteeing the uniformity of the subsequent solvent evaporation process. Therefore, during the evaporation process, the solvent evaporation rates at the top and bottom of the textured structure are similar, avoiding rapid evaporation at the top of the textured structure and exposure of the top tip, which could lead to a decrease in device performance. Ultimately, a carrier transport layer of uniform thickness is formed.

[0061] This application also provides a method for fabricating a solar cell, which includes the aforementioned method for fabricating a contoured carrier transport layer.

[0062] In one specific implementation, such as Figure 2 As shown, the solar cell is a perovskite-silicon heterojunction tandem solar cell, comprising a silicon heterojunction cell, a composite layer 8, and a perovskite cell stacked sequentially. The perovskite-silicon heterojunction tandem solar cell includes a first metal electrode 1, a first transparent conductive layer 2, a first doped layer 3, a first passivation layer 4, a silicon substrate 5, a second passivation layer 6, a second doped layer 7, a composite layer 8, a first carrier transport layer 9, a contoured perovskite thin film 10, a second carrier transport layer 11, a buffer layer, a second transparent conductive layer 12, and an antireflection layer stacked sequentially. A second metal electrode 13 penetrates the antireflection layer and is connected to the second transparent conductive layer 12.

[0063] Specifically, the first carrier transport layer 9 is a contoured carrier transport layer, and the second carrier transport layer 11 can be a contoured carrier transport layer or a normal non-contoured carrier transport layer.

[0064] Specifically, the first carrier transport layer 9 can be either a hole transport layer or an electron transport layer, and the conductivity types of the first carrier transport layer 9 and the second carrier transport layer 11 are opposite. When the first carrier transport layer 9 is a hole transport layer, it can be a cuprous oxide layer, a molybdenum oxide layer, a [bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) layer, a copper iodide layer, or a Spiro-OMeTAD (2,2',7,7'-Tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene) layer, a PEDOT layer, a PEDOT:PSS layer, a P3HT layer, a P3OHT layer, a P3ODDT layer, a NiOx layer, or a CuSCN layer. The second carrier transport layer 11 is an electron transport layer, which can be a titanium oxide layer, a tin oxide layer, a C60 layer or a C60-PCBM layer,

[60] PCBM ([6,6]-phenyl-C61 butyric acid methyl ester, Chinese name is [6,6]-phenyl-C61-butyric acid isomethyl ester),

[70] PCBM ([6,6]-Phenyl-C71-butyric acid methyl ester, Chinese name is [6,6]-phenyl-C71-butyric acid isomethyl ester), bis

[60] PCBM (Bis(1-[3-(methoxycarbonyl)propyl]-1-phenyl)-[6,6]C62) layer,

[60] ICBA (1',1″,4',4″-Tetrahydro-di[1,4]methanonaphthaleno[1,2:2',3',56,60:2″,3″][5,6]full Layers such as erene-C60, including but not limited to these, are acceptable as long as they can achieve the functions described in this application.

[0065] When the first carrier transport layer 9 is an electron transport layer, it can be a titanium oxide layer, a tin oxide layer, a C60 layer or a C60-PCBM layer,

[60] PCBM ([6,6]-phenyl-C61 butyric acid methyl ester, Chinese name is [6,6]-phenyl-C61-butyric acid isomethyl ester) layer,

[70] PCBM ([6,6]-Phenyl-C71-butyric acid methyl ester, Chinese name is [6,6]-phenyl-C71-butyric acid isomethyl ester) layer, bis

[60] PCBM (Bis(1-[3-(methoxycarbonyl)propyl]-1-phenyl)-[6,6]C62) layer,

[60] ICBA (1',1″,4',4″-Tetrahydro-di[1,4]methanonaphthaleno[1,2:2',3',56,60:2″,3″][5,6]full The second carrier transport layer 11 is a hole transport layer, which can be a cuprous oxide layer, a molybdenum oxide layer, a [bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) layer, a copper iodide layer, or a Spiro-OMeTAD (2,2',7,7'-Tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene) layer, a PEDOT layer, a PEDOT:PSS layer, a P3HT layer, a P3OHT layer, a P3ODDT layer, a NiOx layer, or a CuSCN layer. These are included, but not limited to, as long as they achieve the functions described in this application.

[0066] The thickness of the first carrier transport layer 9 is 10-15 nm, for example, it can be 10 nm, 11 nm, 12 nm, 13 nm, 14 nm or 15 nm.

[0067] The thickness of the second carrier transport layer 11 is 10-15 nm, for example, it can be 10 nm, 11 nm, 12 nm, 13 nm, 14 nm or 15 nm.

[0068] The buffer layer is used for the longitudinal transport of charge carriers and at the same time protects the perovskite absorber layer from sputtering damage in subsequent PVD processes. It can be a SnO2 layer or a TiO2 layer with a thickness of 5-30nm, for example, it can be 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm or 30nm.

[0069] Both the first transparent conductive layer 2 and the second transparent conductive layer 12 can be transparent conductive films, specifically fluorine-doped tin oxide (FTO), indium tin oxide (ITO), or aluminum-doped zinc oxide (AZO), etc.; the thickness of the transparent conductive layer is 1-20nm, for example, it can be 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, or 20nm.

[0070] The first metal electrode 1 and the second metal electrode 13 layers can both be made of one or more of the following materials: metal materials such as Ag, Au, Cu, Al, Ni, C materials, and polymer conductive materials.

[0071] The antireflective layer can be made of MgF2, LiF, SiO2, etc., with a thickness of 50-300nm, for example, 50nm, 100nm, 150nm, 200nm, 250nm or 300nm.

[0072] The silicon substrate 5 can be an n-type silicon wafer with a textured surface, such as a commercial-grade M2 ​​n-type silicon wafer.

[0073] In this application, the solar cell is a method for fabricating a perovskite-silicon heterojunction tandem solar cell, comprising the following steps:

[0074] Step 1: Fabrication of silicon heterojunction solar cells;

[0075] Step 1a: The silicon wafer is sequentially polished, texturized, coated, and cleaned to form a silicon substrate 5.

[0076] Specifically, commercial-grade M2 ​​n-type silicon wafers are used, and an n-type silicon substrate with a textured surface structure is formed by alkaline solution polishing, texturing, and cleaning.

[0077] Step 1b: Passivation layers, namely the first passivation layer 4 and the second passivation layer 6, are prepared on both sides of the silicon substrate 5.

[0078] Specifically, intrinsic amorphous silicon passivation layers are deposited sequentially on the front and back sides of the n-type silicon substrate 5 in a plasma-enhanced chemical vapor deposition (PECVD) apparatus, i.e., the first passivation layer 4 is the first intrinsic amorphous silicon passivation layer, and the second passivation layer 6 is the second intrinsic amorphous silicon passivation layer.

[0079] Step 1c: A second doped layer 7 is formed on the side of the second passivation layer 6 facing away from the silicon substrate 5.

[0080] Specifically, an n-type amorphous silicon emitter is deposited on the side of the second passivation layer 6 facing away from the silicon substrate 5 using a hydrogen-diluted phosphine and silane mixture.

[0081] Step 1d: A first doped layer 3 is formed on the side of the first passivation layer 4 facing away from the silicon substrate 5.

[0082] Specifically, a p-type amorphous silicon back field is deposited on the side of the first passivation layer 4 facing away from the silicon substrate 5 using a hydrogen-diluted mixture of diborane and silane gas.

[0083] Step 2: Form a composite layer 8 on the surface of the second doped layer 7 that is opposite to the second passivation layer 6.

[0084] Specifically, a TCO thin film was prepared as the composite layer 8 using a magnetron sputtering device.

[0085] Step 3: Fabrication of perovskite solar cells

[0086] Step 3a: A first carrier transport layer 9 is formed on the surface of the composite layer 8 facing away from the second doped layer 7;

[0087] Step 3b: Form a contoured perovskite thin film 10 on the surface of the first carrier transport layer 9 facing away from the composite layer 8;

[0088] Step 3c: A second carrier transport layer 11 is formed on the surface of the contoured perovskite thin film 10 facing away from the first carrier transport layer 9;

[0089] Step 3d: A buffer layer is deposited on the surface of the second carrier transport layer 11 facing away from the contoured perovskite film 10 using an atomic layer deposition device.

[0090] Step 3e: A transparent conductive layer is deposited on the side of the buffer layer away from the second carrier transport layer 11 and on the side of the first doped layer 3 away from the first passivation layer 4. The transparent conductive layer on the side of the buffer layer is the second transparent conductive layer 12, and the transparent conductive layer on the side of the first doped layer 3 is the first transparent conductive layer 2.

[0091] Step 3f: A second metal electrode 13 is formed by vapor deposition using a mask method on the surface of the second transparent conductive layer 12 facing away from the buffer layer. Simultaneously, a first metal electrode 1 is formed by vapor deposition using a mask method on the surface of the first transparent conductive layer 2 facing away from the first doped layer 3.

[0092] Step 8: An anti-reflection film is prepared on the front side (perovskite side) using electron beam evaporation to reduce light reflection on the cell surface, thereby obtaining the two-dimensional and three-dimensional bulk hybrid perovskite solar cell.

[0093] Step eight is optional.

[0094] The fabrication methods for the first and second carrier transport layers in the perovskite-silicon heterojunction tandem solar cell can refer to the description of the aforementioned fabrication method for the contoured carrier transport layer.

[0095] In step 3b, the method for preparing the contoured perovskite thin film includes the following steps:

[0096] Step 3b1: Prepare the perovskite precursor solution;

[0097] Step 3b2: Coat the perovskite precursor liquid onto the first carrier transport layer having a textured surface;

[0098] Step 3b3: Flip the device coated with the perovskite precursor solution so that the surface coated with the perovskite precursor solution is facing down, so that the perovskite precursor solution flows downward along the textured surface under the action of gravity.

[0099] Step 3b4: Vacuum treatment and annealing are used to form a perovskite film with a textured surface.

[0100] In step 3b1, the perovskite precursor solution is prepared by mixing the perovskite precursor material with a solvent and additives, so that the perovskite precursor material dissolves in the solution composed of the solvent and additives.

[0101] Specifically, the perovskite precursor material is selected from two or more of FAI, MAI, FABr, MABr, FACl, MACl, PbI2, PbBr2 or PbCl2.

[0102] In some embodiments, the solvent is composed of a main solvent and an auxiliary solvent, and the mass ratio of the main solvent to the auxiliary solvent m is ≥ 9:1, for example, it can be 9:1, 9.1:1, 9.2:1, 9.3:1, 9.4:1, 9.5:1, 9.6:1, 9.7:1, 9.8:1, 9.9:1, 10:1, 20:1, 30:1, etc.

[0103] In some embodiments, the solvent consists only of the main solvent.

[0104] The main solvent is selected from one or more of dimethoxyethanol, ethanol, isopropanol, and water;

[0105] The auxiliary solvent is selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, 1-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolinone, and hexamethylphosphoric triamine.

[0106] The solvent contains a small amount of Lewis base as an auxiliary solvent. The Lewis base forms an intermediate phase with the perovskite precursor material, which is beneficial for the slow crystallization of the perovskite film and improves the crystal quality and device performance.

[0107] The additive is selected from one of the following: acetonitrile, ammonium acetate, methylamine acetate, ethylamine acetate, formamidine acetate, formic acid amine, methylamine formate, urea, thiourea, carbazole and its derivatives, thiophene and its derivatives, pyridine and its derivatives, piperazine and its derivatives, and lecithin.

[0108] Specifically, the concentration of the perovskite precursor solution (the concentration of the perovskite precursor solution is the concentration of the perovskite precursor material) is not greater than 1.5 mM, preferably 1.2 mM. For example, it can be 1.5 mM, 1.4 mM, 1.3 mM, 1.2 mM, 1.1 mM, 1.0 mM, etc.

[0109] In some embodiments, the concentration of the perovskite precursor solution is 0.5 mM to 1.5 mM.

[0110] Specifically, the viscosity of the main solvent is no greater than 5 mPa·s, preferably between 0.5 mPa·s and 2 mPa·s. For example, it can be 5 mPa·s, 4 mPa·s, 3 mPa·s, 2 mPa·s, 1 mPa·s, 0.9 mPa·s, 0.8 mPa·s, 0.7 mPa·s, 0.6 mPa·s, 0.5 mPa·s, 0.4 mPa·s, 0.3 mPa·s, etc.

[0111] To reduce the viscosity of the solvent, the solution can be heated, with the heating temperature ranging from 25°C to 60°C.

[0112] The boiling point of the main solvent is not higher than 130°C, preferably 130°C. For example, it can be 130°C, 125°C, 120°C, 115°C, 110°C, etc.

[0113] In some embodiments, the boiling point of the main solvent is 80-130°C.

[0114] In step 3b2, as Figure 3As shown, when the perovskite precursor liquid is spin-coated onto a substrate with a textured surface, the spin-coating rate n ≤ 1500 / rpm, preferably 1000 rpm, and the spin-coating time t ≤ 10s, preferably t ≤ 2s.

[0115] Specifically, the spin coating rate n can be 1500 / rpm, 1400 / rpm, 1300 / rpm, 1200 / rpm, 1100 / rpm, 1000 / rpm, 800 / rpm, 700 / rpm, 600 / rpm, 500 / rpm, etc.

[0116] Specifically, the spin coating time t can be 5s, 4.5s, 4s, 3.5s, 3s, 2.5s, 2s, 1.5s, 1s, etc.

[0117] The height of the liquid film is controlled by the spin coating rate and spin coating time. Under the condition of constant spin coating time, if the spin coating rate is too high, the liquid film height will decrease, and if the spin coating rate is too low, the liquid film height will increase. Under the condition of constant spin coating rate, if the spin coating time is increased, the liquid film height will decrease, and if the spin coating time is shortened, the liquid film height will increase.

[0118] The lower the spin-coating rate and the shorter the spin-coating time of the perovskite precursor solution, the thicker the final perovskite film will be.

[0119] Specifically, the height h1 of the velvet structure is 1-10 μm, preferably 5 μm, and can be, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm.

[0120] Specifically, the shape of the velvet structure is selected from one or more of the following: columnar, conical, frustum-shaped, arc-shaped groove, or arc-shaped protrusion. For example, it can be a forward or reverse triangular prism, quadrangular prism, hexagonal prism, cylindrical, conical, triangular pyramidal, quadrangular pyramidal, frustum-shaped, triangular frustum-shaped, quadrangular frustum-shaped, as well as a semi-circular arc-shaped groove or semi-circular arc-shaped protrusion.

[0121] The velvet structure can be composed of one or more of the following: columnar, conical, truncated, arc-shaped grooves, or arc-shaped protrusions.

[0122] In one specific embodiment, the velvet structure is conical.

[0123] In steps 3b3 and 3b4, a fixture is used to quickly flip the substrate coated with the perovskite precursor solution, placing it face down in a vacuum extraction chamber. A vacuum pump is then started, with the extraction pressure below 10 Pa and the extraction time between 1 and 30 seconds. During extraction, due to the low viscosity of the perovskite precursor solution, it flows downwards along the pyramid surface under gravity. As the main solvent evaporates during extraction, the perovskite precursor solution solidifies into a perovskite mesophase film with a textured surface. The mesophase film is composed of PbX2·FAX·MAX·DMSO.

[0124] Specifically, the substrate flipping speed is 30° / s-180° / s, for example, it can be any value among 30° / s, 40° / s, 50° / s, 60° / s, 70° / s, 80° / s, 90° / s, 100° / s, 110° / s, 120° / s, 130° / s, 140° / s, 150° / s, 160° / s, 170° / s, and 180° / s.

[0125] Specifically, after the evacuation is completed, the substrate is flipped so that the side coated with the perovskite precursor liquid faces upward, and it is placed on a hot plate for annealing. The annealing conditions are between 100-150°C and the annealing time is 20-30 minutes. After annealing, a perovskite film is formed.

[0126] The perovskite film is MAPbI3, FAPbI3, or (Cs) 0.15 FA 0.85 )Pb(I 0.7 Br 0.3 The component system has an average thickness of 350-500nm, for example, it can be 350nm, 360nm, 370nm, 380nm, 390nm, 400nm, 410nm, 420nm, 430nm, 440nm, 450nm, 460nm, 470nm, 480nm, 490nm or 500nm.

[0127] Specifically, the height difference between the thicknesses of several points randomly selected on the perovskite film is Δ, where |Δ|≤10%.

[0128] In this application, by rapidly flipping the device coated with the perovskite precursor liquid so that the surface coated with the perovskite precursor liquid faces downward, the perovskite precursor liquid is allowed to flow downward along the textured surface under the action of gravity, thereby obtaining a perovskite film with uniform coverage and uniform thickness that mimics the pyramid shape.

[0129] Example

[0130] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0131] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.

[0132] Example 1

[0133] The fabrication method of the perovskite-silicon heterojunction tandem solar cell in this embodiment includes the following steps:

[0134] Step 1: Fabrication of silicon heterojunction solar cells

[0135] Step 1a: A commercial grade M2 ​​n-type silicon wafer with a thickness of 180μm and a resistivity of 5Ω·cm is used. The wafer is polished with an alkaline solution, texturized, and cleaned to form an n-type silicon substrate with a textured surface structure. The height h1 of the textured surface structure is 5μm.

[0136] Step 1b: Using a plasma-enhanced chemical vapor deposition (PECVD) device, 10 nm intrinsic amorphous silicon passivation layers are deposited sequentially on the front and back sides of an n-type silicon substrate, respectively. That is, the first passivation layer is the first intrinsic amorphous silicon passivation layer, and the second passivation layer is the second intrinsic amorphous silicon passivation layer.

[0137] Step 1c: Deposit an n-type amorphous silicon emitter with a thickness of 10 nm on the side of the second passivation layer away from the silicon substrate using a hydrogen-diluted phosphine and silane mixed gas.

[0138] Step 1d: Deposit a 15 nm thick p-type amorphous silicon back field on the side of the first passivation layer away from the silicon substrate using a hydrogen-diluted mixture of diborane and silane gas.

[0139] Step 2: Preparation of the composite layer

[0140] A TCO thin film with a thickness of 10 nm was prepared on the surface of the n-type amorphous silicon emitter away from the second passivation layer using a magnetron sputtering apparatus.

[0141] Step 3: Fabrication of perovskite solar cells

[0142] Step 3a: Fabrication of the first carrier transport layer

[0143] 2PACz self-assembled molecules were dissolved in an ethanol solution to form a 2PACz solution with a concentration of 1 mg / ml. The 2PACz solution was then spin-coated onto the surface of the TCO film using a spin coater at 1000 rpm for 10 seconds. A polyvinyl chloride (PVC) film was then used to cover the surface of the TCO film, and the device was placed on a hot plate at 50°C. The PVC film was slowly lifted from one end, and after it was removed from the TCO film surface, the device was placed on a hot plate at 100°C for annealing for 10 minutes, thereby forming a uniformly contoured first carrier transport layer (hole transport layer) with a thickness of approximately 1 nm.

[0144] Step 3b: Form a contoured perovskite thin film on the surface of the first carrier transport layer facing away from the composite layer;

[0145] Specifically, a perovskite precursor solution was prepared. CsI, FAI, MABr, and PbI2 were mixed according to the Cs... 0.05 FA 0.8 MA 0.15 PbBr 0.6 I 2.4 The components were weighed and dissolved to obtain a 1.2 mM perovskite precursor solution. The primary solvent was dimethoxyethanol, and the secondary solvent was dimethyl sulfoxide (DMSO), with a volume ratio of 9:1. Additionally, 0.05 mM lecithin was added. The perovskite precursor solution was then vigorously stirred at room temperature for more than 12 hours before use.

[0146] Place the substrate obtained in step 3a on a spin coater and take 100 μl of a 1.2 mM perovskite precursor solution. The perovskite precursor solution is composed of (Cs) 0.05 FA 0.8 MA 0.15 PbBr 0.6 I 2.4 The perovskite precursor material was dissolved in a solution of dimethoxyethanol and dimethyl sulfoxide in a volume ratio of 5:1. The solution was spin-coated at 1000 rpm for 10 seconds. After spin-coating, the solution was immediately placed in a fixture with the liquid film containing the perovskite precursor solution facing down. The fixture was then immediately placed in a vacuum chamber and a vacuum process was initiated. The pressure in the vacuum chamber was reduced to 1 Pa within 10 seconds. After holding for 10 seconds, the substrate was removed and annealed on a hot plate at 120°C for 30 minutes to form a perovskite film with a textured surface. The thickness of the perovskite film on the slope of the textured surface was 420 nm ± 3%.

[0147] Step 3c: Fabrication of the second carrier transport layer

[0148] First use The evaporation rate is such that 1 nm of LiF is deposited on the surface of the perovskite film on the side opposite to the first carrier transport layer, and then... A 10 nm C60 layer was deposited at an evaporation rate as an electron transport layer.

[0149] Step 3d: Prepare the buffer layer

[0150] A 10 nm SnO2 layer was prepared on the side of the second carrier transport layer away from the perovskite film using an atomic layer deposition apparatus.

[0151] Step 3e: Prepare the first transparent conductive layer and the second transparent conductive layer.

[0152] A 110 nm ITO thin film was deposited on both the side of the buffer layer away from the second carrier transport layer and the side of the p-type amorphous silicon back field away from the first passivation layer by magnetron sputtering.

[0153] Step 3f: Fabrication of metal electrodes

[0154] A 200nm silver grid electrode was deposited on an ITO thin film using a masking method to obtain a perovskite-silicon heterojunction tandem solar cell. The parameters are shown in Table 1, and the electron microscopy image of the perovskite thin film after formation is shown in the figure. Figure 1 .

[0155] The only difference between Examples 2-6 and Example 1 is the concentration of the 2PACz solution. The parameters of the solar cells in this example are shown in Table 1.

[0156] The only difference between Examples 7-11 and Example 1 is the thickness of the flexible film. The parameters of the solar cell in this example are shown in Table 1.

[0157] The only difference between Examples 12-17 and Example 1 is the rate at which the flexible film is peeled off. The parameters of the solar cell in this example are shown in Table 1.

[0158] The only difference between Examples 18-21 and Example 1 is the material of the flexible film. The parameters of the solar cell in this example are shown in Table 1.

[0159] The only difference between Examples 22-25 and Example 1 is the hole transport material. The parameters of the solar cells in this example are shown in Table 1.

[0160] The only difference between Example 26 and Example 1 is the hole transport material. The parameters of the solar cell in this example are shown in Table 1.

[0161] The only difference between Examples 27-29 and Example 26 is the concentration of the hole transport material solution. The parameters of the solar cell in this example are shown in Table 1.

[0162] The only difference between Comparative Example 1 and Example 1 is that the hole transport layer does not use a flexible film during its formation (i.e., there is no process of peeling off the flexible film). The parameters of the solar cell in this example are shown in Table 1.

[0163] Table 1 shows the performance of the solar cells in each embodiment and comparative example.

[0164]

[0165]

[0166] Summary: As shown in Table 1, the solar cell prepared by the method of this application involves coating a hole transport material solution onto a substrate with a textured surface, covering the surface of the solution with a flexible film, and slowly peeling off the flexible film during heating. Due to the surface tension, the solution adheres between the flexible film and the substrate, making the amount of solution at the top and bottom of the textured structure similar. Therefore, during the evaporation process, the solvent evaporation rates at the top and bottom of the textured structure are similar, ultimately forming a uniformly thick contoured hole transport layer, thereby enabling the solar cell to have better performance.

[0167] Although the embodiments of this application have been described above in conjunction with the specific embodiments described, this application is not limited to the specific embodiments and application fields described above. The specific embodiments described above are merely illustrative and instructive, and not restrictive. Those skilled in the art can make many other forms based on the teachings of this specification and without departing from the scope of protection of the claims of this application, and these are all within the scope of protection of this application.

Claims

1. A method for fabricating a contoured carrier transport layer, characterized in that, Includes the following steps: A solution of charge carrier transport material is coated onto a substrate with a textured surface. A flexible thin film is covered on the surface of the carrier transport material solution and then heated; During the heating process, the flexible film is peeled off from one side and detached along the textured surface. The solvent in the carrier transport material solution between the flexible film and the substrate evaporates, and the solute precipitates and deposits on the textured surface of the substrate to form a carrier transport layer.

2. The preparation method according to claim 1, characterized in that, The carrier transport layer is either a hole transport layer or an electron transport layer.

3. The preparation method according to claim 1, characterized in that, The concentration of the carrier transport material solution is 0~200 mg / ml, but does not include 0.

4. The preparation method according to claim 1, characterized in that, The carrier transport material solution includes a solvent and a carrier transport material. The solvent is selected from one or more of ethanol, isopropanol, 2-butanol, water, diethyl ether, 2-methoxyethanol, ethyl acetate, methyl acetate, methyl formate, ethyl formate, tetrahydrofuran, acetonitrile, and chlorobenzene.

5. The preparation method according to claim 4, characterized in that, The charge carrier transport material is selected from SnO2, ZnO, TiO2, PCBM, and C. 60 One or more of NiO, 2PACz, 4PACz, Me-2PACz, Me-4PACz, Me-6PACz, MeO-2PACz, MeO-4PACz, MeO-6PACz, spiro-OMeTAD, and PTAA.

6. The preparation method according to claim 1, characterized in that, The height of the velvet structure is 1-10 μm.

7. The preparation method according to claim 1, characterized in that, The thickness of the flexible film is no more than 1 mm; and / or the maximum bending radius of the flexible film is no more than 100 cm.

8. The preparation method according to claim 1, characterized in that, The flexible film is selected from polymer flexible film or metal flexible film.

9. The preparation method according to claim 1, characterized in that, After the flexible film is covered on the surface of the carrier transport material solution, it is placed on a heating plate at 50~100°C for heating. During the heating process, the flexible film is peeled off at a certain rate. Due to the surface tension, the carrier transport material solution adheres between the flexible film and the substrate, making the solution volume at the top and bottom of the textured structure on the substrate similar, thereby forming a uniformly thick contoured carrier transport layer.

10. The preparation method according to claim 9, characterized in that, The rate at which the flexible film is peeled off is not less than 1 cm / min.

11. A method for preparing a solar cell, characterized in that, The method for preparing the contoured carrier transport layer as described in any one of claims 1-10.

Citation Information

Patent Citations

  • Flexible printed circuit board and manufacturing method thereof and method for manufacturing substrate for liquid crystal panel

    CN103909757A

  • Method for preparing perovskite thin film and solar cell on suede substrate based on solution method

    CN113437220A